Application of Ultrasonic Velocity Profiler (UVP) in the Vortex-induced Vibration Experiments - Sharul Sham Dol (Novel Perspectives of Engineering Research Vol. 4, 2021)
An ultrasonic velocity profiler, UVP was used to study the flow properties in the near wake of the rigid and flexible protruding surface. Experiments were conducted in a water tunnel. The performance of turbulence enhancement depends heavily on the motion of the cylinder. An organized oscillating motion is in favor of a higher performance of turbulence enhancement. This research work has provided useful insights of the turbulence characteristics of flow around the fully three-dimensional flexible cantilever, in which the combination of two or three UVP probes are capable in measuring three velocity components.